Performance Analysis of Signalized Intersection Due to Opening of Jatikarya Exit Access to Cimanggis – Cibitung Toll Segment Using PTV Vissim Software - Reyhan Febrian Putra; Eva Azhra Latifa (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
The development of infrastructure, especially road construction, also has an impact on changes in various urban systems in an area. Developments in the transportation system, including the opening of toll road access, will certainly affect increasing traffic flow. With the opening of toll road access, it creates new intersections so that the Cibubur Alternative Road experiences a high increase, especially during peak hours. This study aims to determine the effect of access to the Cimanggis-Cibitung toll road on the performance of the Cibubur Alternative Road. The study begins with collecting data according to the parameters needed as the basis for analyzing road performance, namely the degree of saturation and the level of service based on the 2014 PKJI by comparing the conditions and assumptions of normal conditions (by dividing 75% of the existing conditions). The results of the analysis show that the highest degree of saturation is on Alternative Cibubur Road 0.74 and if it is assumed under normal conditions it is 0.99 (the lowest service level is E with the lowest speed reaching 30.0 km/hour), queue length 194.47 meters and delays time. Reaching 109.87 seconds indicates a conflict at the signalized intersection because the queue length affects the performance of the Cibubur alternative road. After doing the simulation and getting an effective intersection optimization, namely resetting the green time with VISSIM software modeling, it gives better results during peak hours and reduces the highest queue length by 56,58% and delays by 80,16%.